PERAN KOMUNIKASI EFEKTIF DALAM KEPEMIMPINAN DEMOKRATIS DI SMK SCIENCE TECHNOLOGY AND BUSINESS (STB) SAWANGAN - Imambachri, Sapto Hadi; Turkamun, Turkamun; Darmawan, Deni; Junaedi, Edi; Sumadikarta, Ismul Bathni (Universiitas Pamulang, 2021)
ABSTRACT Various studies have been carried out aimed at knowing effective communication models and leadership models in an organization. Bartol (2008: 505) states that